A 'KAHOOT!' Approach: The Effectiveness of Game-Based Learning for an Advanced Placement Biology Class. (December 2019) - Jones, Serena M.; Katyal, Priya; Xie, Xuan; Nicolas, Madeleine P.; Leung, Eric M.; Noland, Damon M.; Montclare, Jin Kim
Background. Keeping high school students engaged and motivated to learn complex scientific concepts can be difficult and challenging; this is especially true if the task feels daunting and unfamiliar to the students. Incorporating educational technology, such as KAHOOT, into the classroom can help students learn scientific material even when it is difficult. Aim. Our objective is to determine the effectiveness ofgamification in anAdvanced Placement Biology (AP biology) classroom by using the online game'KAHOOT!' as a supplement to traditional teacher-centered learning. In addition, we determine the use of'KAHOOT!' in enhancingstudent engagement and the learning experience for biology. Methods. A presentation on Transcription and Translation was given to a small group of high schoolAP Biology students ( n = 18, 18 women). After the presentation, the students were given 15 questions and twenty seconds to answer each question in the'KAHOOT!' game. Both the students and the teacher were given a post-activity survey to assess their interest in the activity. Results. Based on the responses in the Students' Survey, 'KAHOOT!' can be used as a gamified assessment tool to help students learn the topic of 'Transcription and Translation' by actively engaging them in a fun and exciting manner. Conclusion. The overall activity had a positive impact on the students and teacher as the students enjoyed learning Transcription and Translation through the use of 'KAHOOT!'.